Enhancing Arabic Speaking Skills through the Werewolf Role-Playing Game: A Psycholinguistic and Pragmatic Approach - Asep Sunarko; Masnun; Nur Aunie Batrisya (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
Despite growing evidence supporting game-based learning in second-language education, research on non-digital social deduction games for Arabic speaking development remains limited, particularly from integrated psycholinguistic and pragmatic perspectives in Islamic boarding school contexts. This study investigates the effectiveness of the Werewolf role-playing game in enhancing Arabic speaking proficiency through psycholinguistic and pragmatic lenses. Employing a mixed-methods one-group pretest–posttest design, the study involved 30 students at Darullughah Wadda’wah Islamic Boarding School who participated in twelve weekly Werewolf sessions within a maharah kalām course. Data were collected through speaking tests, classroom observations, audio recordings, reflective journals, and semi-structured interviews, and analyzed using Krashen’s Affective Filter Hypothesis, Levelt’s speech production model, and Searle’s speech act theory. The findings indicate a 43% improvement in students’ fluency and confidence scores from pre-test to post-test. The game reduced speaking anxiety, increased spontaneous lexical retrieval, and encouraged active participation in Arabic interaction. Pragmatic analysis revealed the frequent emergence of assertive (31%), directive (28%), expressive (18%), commissive (14%), and declarative (9%) speech acts, demonstrating learners’ growing ability to persuade, negotiate, justify, and manage conversational exchanges. This study proposes a psychopragmatic model of Arabic speaking development in which affective engagement, real-time speech processing, and pragmatic meaning-making interact within a culturally grounded learning environment, highlighting the pedagogical potential of non-digital role-playing games for authentic Arabic communication.